2020
DOI: 10.1016/j.rbmo.2020.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Controversy in the management of oestrogen therapy before hysteroscopic adhesiolysis: a systematic review and meta-analysis

Abstract: Preoperative oestrogen therapy may improve the short-term prognosis of intrauterine adhesions, but evidence of an effect on subsequent reproductive outcomes is insufficient. The quality of evidence was moderate to very low for all outcomes. More strictly designed studies are needed to assess the effectiveness of oestrogen administration before hysteroscopic adhesiolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Nor through the oral estrogen administration have better results been obtained [ 137 , 139 , 140 ]. A recent systematic review and meta-analysis conducted by Chang et al [ 141 ] also exposed the relatively low efficiency of estrogen therapy, the quality of evidence ranging from moderate to very low with only a short-term or negative effect.…”
Section: Introduction Our Current Knowledge About the Asherman Symentioning
confidence: 99%
“…Nor through the oral estrogen administration have better results been obtained [ 137 , 139 , 140 ]. A recent systematic review and meta-analysis conducted by Chang et al [ 141 ] also exposed the relatively low efficiency of estrogen therapy, the quality of evidence ranging from moderate to very low with only a short-term or negative effect.…”
Section: Introduction Our Current Knowledge About the Asherman Symentioning
confidence: 99%
“…A recent systematic review and meta-analysis concluded that preoperative estrogen treatment did not change the long-term prognosis and fertility outcome of treated patients. 26 However, every group but the group with Class I adhesions received postoperative oral estrogens In our study, all patients with Class 2-5 adhesions received intrauterine hyaluronic acid gel application after adhesiolysis.…”
Section: Advantages and Limitations Of Different Classification Systemsmentioning
confidence: 71%
“… 9 This can be attributed to a suboptimal regeneration of functional endometrum. 10 The transplantation of mesenchymal stem cells (MSCs) into the uterine cavity could efficiently induce endometrial regeneration and remove IUAs. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%